1985
DOI: 10.1016/0035-9203(85)90384-0
|View full text |Cite
|
Sign up to set email alerts
|

Egg count variability and sensitivity of a thin smear technique for the diagnosis of Schistosoma mansoni

Abstract: Variation in daily egg counts, and in counts for samples of the same stool, was investigated in children with Schistosoma mansoni and Ascaris lumbricoides infections, using a thin smear technique. The results indicated that counts vary according to the stool consistency; drier stools from the same person producing up to seven times greater counts than wet ones. The sensitivity of the technique was tested in schoolchildren living in an endemic S. mansoni area, and found to detect all infections with intensities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 10 publications
0
24
1
Order By: Relevance
“…5 However, this assay offers poor sensitivity, especially in lowintensity infections, is laborious, and may expose workers to infectious stool. [5][6][7][8][9][10][11] To address some of the concerns with the Kato-Katz technique, considerable research has been devoted to alternative tests for S. mansoni infections. This research has led to the development of a urine-based point-of-contact test for schistosome circulating cathodic antigen (POC-CCA) as a method for detecting infection with S. mansoni.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, this assay offers poor sensitivity, especially in lowintensity infections, is laborious, and may expose workers to infectious stool. [5][6][7][8][9][10][11] To address some of the concerns with the Kato-Katz technique, considerable research has been devoted to alternative tests for S. mansoni infections. This research has led to the development of a urine-based point-of-contact test for schistosome circulating cathodic antigen (POC-CCA) as a method for detecting infection with S. mansoni.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, using the Kato-Katz method, samples from different days showed only a 6% positivity increase compared with the first sample. 10 We are thus faced with a challenge both in the individual and collective context, because this is a chronic infection that, even without progressing to severe forms, triggers debilitating sequelae secondary to parasitism, especially in childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Although the examination of more samples of feces increase the probability of schistosomiasis diagnosis, the quantitative reproducibility of the Kato-Katz method has shown variations, especially when the amount of S. mansoni eggs is low (Kong et al 2001). Teesdale et al (1985) and Engels et al (1996) judge that due to the daily variation of the number of eggs, the analysis with two smears would be enough in order to increase the sensibility of the method. Teesdale et al (1985) found that only 6% of positive samples were identified after a second exam accomplished in different days, suggesting that for epidemiological purposes, the effort and logistics to obtain two samples of a same person are not worthwhile.…”
Section: Schistosomiasis Applied Diagnosis In Venezuelamentioning
confidence: 99%
“…Teesdale et al (1985) and Engels et al (1996) judge that due to the daily variation of the number of eggs, the analysis with two smears would be enough in order to increase the sensibility of the method. Teesdale et al (1985) found that only 6% of positive samples were identified after a second exam accomplished in different days, suggesting that for epidemiological purposes, the effort and logistics to obtain two samples of a same person are not worthwhile.…”
Section: Schistosomiasis Applied Diagnosis In Venezuelamentioning
confidence: 99%